DAMPAK STRUKTUR KEPEMILIKAN DAN PROFITABILITAS TERHADAP KEBIJAKAN HUTANG DENGAN KEBIJAKAN DEVIDEN SEBAGAI VARIABEL PEMODERASI - Sulhan, Muhammad; Nurillah, Sofi (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
Company funding sources can come from internal funding sources and external funding sources. Internal funds are generated by the company itself such as current profit, retained earnings, and share capital. While external funds come from additional capital participation from owners or issuance of new shares, sale of bonds, credit from banks. If the company meets the needs of its funds, it is fulfilled from funds originating from loans, it is said that the company is financing debt, bothshort-term debt and long-term debt, this will be related to the company's debt policy. This study aims to determine the effect of ownership structure and profitability on debt policy and to determine whether dividend policy can be used as a moderating variable on the relationship of ownership structure and profitability to debt policy.This study uses quantitative research. The population in this study are property, real estate and building construction companies in 2014-2016. The sample in this study was taken by purposive sampling technique, which amounted to 23 companies. The data analysis technique used in this study is Moderating Regression Analysis (MRA). The results of this study indicate that the ownership structure and profitability have a significant positive effect on debt policy. In contrast, dividend policy does not affect debt policy. The results also show that dividend policy cannot strengthen or weaken the ownership structure relationship to debt policy. However, dividend policy can weaken the relationship between profitability and debt policy.